Analysis of A Marketing Management MSME Food Products - Kusumaningrum, Anisa Putri; Swantari, Anita; Ryadi, Ragil; Wibowo, Noor Sultan Irgi; Andini, Davi Ayu (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study explores Sabana Fried Chicken, an Indonesian MSME specialising in halal fried chicken. Examining its inception in 2008, vision, mission, and SWOT analysis, the research highlights key factors contributing to its success: unique taste, high-quality ingredients, and effective customer service. Despite strengths, challenges include location limitations and supply dependence. Opportunities for expansion, menu diversification, and delivery services are identified, while threats stem from strong competitors, changing consumer preferences, regulations, and economic conditions. The marketing mix analysis reveals an affordable pricing strategy, strategic outlet locations, limited yet effective promotional activities, and a product focus on halal, delicious, and nutritious offerings. This case study offers insights for MSMEs navigating the dynamic landscape of the fast-food industry.